Actividades interactivas para estudiantes con trastornos de discalculia en la Unidad Educativa Héroes del Cenepa en el año lectivo 2021-2022 - Utitiaj Castillo, Jofre Alexander (2024)
The present research refers to a pedagogical approach based on the determination of the importance in the implementation of interactive activities for students with dyscalculia disorders in the Educational Unit “Heroes del Cenepa” to overcome deficiencies, weaknesses and difficulties immersed in the management of mathematical calculations and logical operations; In addition, a qualitative and quantitative approach is implemented, with critical analysis and a narrative design that takes into account scientific articles and national and international publications of greater relevance and pertinence. The techniques applied were observation and interview with their respective instruments observation guide and questionnaire respectively in order to determine the importance of interactive activities for students with dyscalculia disorder in the educational unit “Heroes del Cenepa”, The application of the semi-structured interview techniques was directed to the teacher and finally to the students. The purpose of the observation technique and the student survey was to gather information in order to obtain the greatest number of numerical data. At the end of the study it was possible to identify that interactive activities strengthen the learning process in students with dyscalculia disorder, which requires a process of practice and constant evaluation by teachers, educational psychologist and parental support.